Analysis of the Strategic Role of MSMEs as a Pillar of the National Economy Amidst Global Dynamics - Nurul Azizah; Ghafiratun Ni’am El Maulidiyah; Mashudi (Penerbit Hellow Pustaka, 2025)
Micro, Small, and Medium Enterprises (MSME) in Indonesia play a vital role in the national economy, particularly in providing employment and contributing to Gross Domestic Product (GDP). This study aims to analyze the strategic role of MSME in supporting Indonesia’s economy amid global dynamics, focusing on the adaptive strategies implemented by MSME owners to respond to various challenges. The research employs a qualitative approach, with data gathered through interviews and literature review. The findings indicate that MSME in Indonesia continue to adapt to technological advancements, such as digital marketing and product innovation, to maintain their competitiveness. However, MSME still face challenges, including limited access to financing, complex regulations, and low levels of financial and digital literacy. The government has introduced various policies to support MSME development, but there is still a gap in their implementation across Indonesia. This study recommends enhancing access to financing, expanding financial and digital literacy training, and enacting more pro-MSME policies to encourage the sustainability and growth of this sector.